الصلح القضائي بين الزوجين في الفقه الإسلامي والتشريع الجزائري - لخذاري، عبدالحق Lakhdhari, Abdulhaq (جامعة باتنه 1 - كلية العلوم الإسلامية, 2020)
الصلح القضائي هو وسيلة ودية لحل النزاعات بين الزوجين المتخاصمين، وهو سبيل في غاية الأهمية من أجل عودة العلاقات الزوجية إلى التفاهم والمودة والرحمة، وهو بذلك يساهم في استقرار الأسرة والأبناء والمجتمع بصورة عامة، إذ أن الأسرة هي الخلية الأساسية للمجتمع، ولا يخفي على أحد اهتمام الفقه الإسلامي بهذا الموضوع فهو مؤصل ومفصل في الكتب الفقهية الإسلامية، وأولى له الفقهاء أهمية بالغة، وفي هذا الإطار أخذ المشرع الجزائري بهذه الوسيلة وتجسد ذلك بالخصوص في قانون الأسرة، حينما فرض على القضاء ضرورة وإلزامية اللجوء إليه قبل رفع دعوى الطلاق وحل الرابطة الزوجية، وهذا دليل على اعتماد المشرع الجزائري على تعاليم الشريعة الإسلامية في مجال الأحوال الشخصية حفاظا على الرابطة الأسرية.
Judicial conciliation is a pacific way to resolve disputes between the hostile spouses, it is a very important way for the return of marital relations to understanding, affection and compassion, thus it contributes to the stability of the family, the children and the society in general, as the family is the basic cell of society, It is no secret that the Islamic jurisprudence is concerned with this subject. It is well-known and detailed in Islamic jurisprudence books thus the jurists gave it great importance. In this context, the Algerian legislator followed this method, and this is reflected especially in Family Law, when he imposed on the judiciary a necessity and an exigency to resort to it before filing a divorce suit and dissolving the marital nexus; this is an evidence of the adoption of the Algerian legislator on the teachings of Islamic law in the field of personal status in order to preserve the family bond.
Keywords: المحاكم الشرعية -- الصلح القضائي -- الفقه الإسلامي -- القوانين والتشريعات -- الجزائر